Nonlinear Modelling of Kinetic Data Obtained from Photocatalytic Mineralisation of 2, 4-Dichlorophenol on a Titanium Dioxide Membrane. (3rd March 2009) - Bellobono, Ignazio Renato; Scotti, Roberto; D'Arienzo, Massimiliano; Morazzoni, Franca; Bianchi, Riccardo; Stanescu, Rodica; Costache, Cristina; Bobirica, Liliana; Cobzaru, Gabriela; Tozzi, Paola Maria; Rossi, Mauro; Bonardi, Mauro Luigi; et al.
Abstract : Photomineralisation of 2, 4-dichlorophenol (DCP) in aqueous solutions (10.0–100.0 mg/L of C) was systematically studied at318 ± 3 K, in an annular laboratory-scale reactor, by photocatalytic membranes immobilizing titanium dioxide, as a function of substrate concentration, and absorbed power per unit length of membrane. Kinetics of both substrate disappearance, to yield intermediates, and total organic carbon (TOC) disappearance, to yield carbon dioxide, were followed (first series of experiments). At a fixed value of irradiance (1.50 W⋅ cm − 1 ), other series of mineralization experiments were repeated (second series of experiments) by carrying out only analyses of chemical oxygen demand (COD), in order to compare modelling results of the two sets of experiments. In both sets of experiments, stoichiometric hydrogen peroxide was used as oxygen donor. For the first series of experiments, a kinetic model was employed, already validated in previous work, from which, by a set of differential equations, four final optimised parameters, k 1 andK 1, k 2 andK 2, were calculated. By these parameters, the whole kinetic profile could be fitted adequately. The influence of irradiance onk 1 andk 2 could be rationalised very well by this four-parameter kinetic model. Modelling of quantum yields, as a function of irradiance, could also be carried out satisfactorily. As has been found previously for other kinds of substrates, modelling of quantum yields for DCP mineralization is consistent with kinetics of hydroxyl radicals reacting between themselves, leading to hydrogen peroxide, other than with substrate or intermediates leading finally to carbon dioxide, paralleled by a second competition kinetics involving superoxide radical anion. For the second series of experiments, on the contrary, the Langmuir-Hinshelwood model was employed. Uncertainties of COD analyses, coupled with discrepancies of this model and with its inability to reproduce kinetics up to complete mineralization, are underlined.